Effect of Particle Loading on the Stability of the Water Based Iron-Oxide Nanofluids - M. Z. Alam, R. Saidur, A. Arifutzzaman, A. F. Ismail, A. A. Khan (International Journal of Advanced Science and Technology, 2020)
Dispersion stability is a crucial challenge for a nanofluid to obtained a uniform dispersion. The main aim of this research is to develop stability monitoring approach by experimental investigation of ultra violet-visible (UV-vis) absorbance of deionized water (DW) based ironoxide (maghemite: MH) nanoparticles dispersed nanofluids (MH/DW). Five different samples were prepared with increasing the loading of MH nanoparticles varied from 0.065 to 0.157 mg/ml in DW. Primarily digital photographs were captured to observed the sedimentation of MH/DW the nanofluids. A method was developed to monitor the quantitative stability of relative concentrations of MH/DW nanofluids. Optical absorbance measurements were conducted using UV-vis absorbance spectroscopy by varying the light wavelength from 200 to 800 nm. Photographs of MH/DW nanofluids after preparation of 25 days shown uniform and there was no precipitation was visible in the suspensions. For a certain loading of MH particle, with the increasing wavelength absorbance was found to be increased. Absorbance peaks were created at wavelength of 360 nm and then decreased monotonically with the increasing wavelength. The relative concentration of the MH/DW nanofluids was declined when increase the precipitation concentration with time due to slight agglomeration. After 600 hours, the minimum and maximum precipitation rates were found 0.27 and 2.5 % for MH/DW nanofluid with the MH concentration of 0.065 and 0.157 mg/ml respectively. Amount of MH nanoparticle loading affects the rate of sedimentations of the produced MH/DW nanofluids.